1981
DOI: 10.1111/j.1365-2621.1981.tb04177.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of the Major Protein from Great Northern Beans (Phaseolus vulgaris)

Abstract: The major protein of Great Northern beans was isolated through salt extraction, ammonium sulfate fractionation, gel filtration and DEAE-cellulose ion exchange chromatography. Physicochemical properties of the major bean protein were determined. Results from heat stability studies showed that the protein was the most stable at pH values between 4 and 6. A complete unfolding of the bean protein was not essential in order to improve its digestibility. The native protein had a compact structure and therefore was r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
2

Year Published

1988
1988
2008
2008

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 27 publications
1
39
0
2
Order By: Relevance
“…These results agreed with the report (Chang and Satterlee, 1981) that the major storage protein of the Great Northern beans contained a glycopeptide which is resistant to the mammalian digestive enzymes and a bacterial protease. Chang (1980) and Chang and Satterlee (1981) showed that a protease-resistant glycopeptide from the major storage protein of Great Northern beans contained a high molar ratio of asparagine. Csoma and Polgar (1984) showed that a purified thiol-endopeptidase developed during germination was highly specific for the asparagine side chain.…”
Section: Trypsin Inhibitor and Lectin Activitysupporting
confidence: 94%
“…These results agreed with the report (Chang and Satterlee, 1981) that the major storage protein of the Great Northern beans contained a glycopeptide which is resistant to the mammalian digestive enzymes and a bacterial protease. Chang (1980) and Chang and Satterlee (1981) showed that a protease-resistant glycopeptide from the major storage protein of Great Northern beans contained a high molar ratio of asparagine. Csoma and Polgar (1984) showed that a purified thiol-endopeptidase developed during germination was highly specific for the asparagine side chain.…”
Section: Trypsin Inhibitor and Lectin Activitysupporting
confidence: 94%
“…A Tabela 8 apresenta a composição aminoacídica das cultivares de feijões cozidos com água de maceração, observando-se que as cultivares são caracterizadas pelo baixo conteúdo de metionina e alto conteúdo de aminoácidos aromáticos (fenilalanina e tirosina), leucina, lisina, ácido aspártico e ácido glutâmico, o que concorda com a literatura (CHANG;SATTERLEE, 1981;SGARBIERI;WHITAKER, 1982).…”
Section: Aminoácidos E Pdcaasunclassified
“…The major storage protein (globulin Gl) of the Great Northern bean was isolated using the procedure described by Chang and Satterlee, (1981). The Gl protein fraction isolated was Characterization of the methionine-containing peptides Peptides released during the digestion of Gl protein were separated, based on their degree of hydrophobicity, using reverse phase HPLC.…”
Section: Chemical Analysismentioning
confidence: 99%
“…Author Romero's current address is Univ. of Sonora, Hermosillo, Sonora, Mexico 83000. ibility for both legume flours and protein concentrates (Sathe et al, 1984;Deshpande et al, 1983;Chang and Satterlee, 1981;Liener and Thompson, 1980;Romero and Ryan, 1978;Bender et al, 1979;Pusztai et al, 1975;Seidl et al, 1969).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation